Living, working conditions and mental health: a study with Brazilian and Spanish workers who work in hospital cleaning services - Alves Rocha, Marcia Regina [UNESP]; Sanches Marin, Maria Jose; Macias-Seda, Juana (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2020)
Objective: To compare living, work and health conditions, with a particular interest in the mental health of Brazilian and Spanish outsourced hospital cleaning workers. Method: This is a cross-sectional, quantitative investigation carried out in two public general hospitals, one in the Brazilian Midwest region of Sao Paulo and the other in the Southwest region of the Iberian Peninsula. In total, 78 Brazilian hospital workers and 39 Spanish hospital workers were interviewed using a script with data on the living conditions, including some validated questionnaires such as the Job Content Questionnaire (JCQ) and Self-Reporting Questionnaire (SRQ-20). Results: Spanish workers are older, white and with a higher household income, with lower SRQ scores in all realms. Also, they smoke more, have a higher level of visual impairment and allergies, have been working in the same activity longer, with a lower workload and do not hold two jobs. Besides, almost 40% of them consider that their work is autonomous. Conclusions: Brazilian workers are subject to more impoverished living, working and mental health conditions than Spanish workers. Only a few aspects of health conditions were worse among Spanish workers, which may probably be related to their advanced age.
Keywords: Worker's health; Mental disorder; Cleaning service